A visual language for programming reality-based interaction. - Shaer, Orit.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
Reality-based interfaces (RBIs) offer the promise of natural interfaces that are intuitive to use. By allowing users to leverage their innate skills and knowledge about the real-physical world, RBIs could benefit disadvantage populations that rely on physical I/O modalities and tangible representations. We present our research which is aimed at simplifying the development of RBIs by providing a technology-independent visual language for modeling and programming these interfaces. Such a language will enable developers to systematically analyze and compare interaction designs as part of the development process while addressing issues such as users' skills and needs. Ultimately, we expect this research to lower the barriers for developing RBIs. © 2006 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.